Deficiency of C1QL1 Reduced Murine Ovarian Follicle Reserve Through Intraovarian and Endocrine Control - Lu, Xiaosheng; Ding, Fei; Chen, Yao; Ke, Shiyun; Yuan, Shaochun; Qiu, Han; Xiao, Luanjuan; Yu, Yanhong (Endocrinology (Philadelphia), 2022)
Ovarian aging is associated with depletion of the ovarian follicle reserve, which is the key determinant of fertility potential in females. In this study, we found that the small, secreted protein complement 1Q-like (C1QL1) is involved in the regulation of follicle depletion through intraovarian and endocrine control in a multidimensional collaborative manner. C1ql1 was detected to be conserved in the ovary and showed high transcript levels during folliculogenesis. Blockade of C1QL1 by IP and ovarian intrabursal injection of C1QL1 antiserum into prepubertal mice impaired folliculogenesis accompanied by reductions in body weight, fat mass, and intraovarian lipid accumulation. An elevation of circulating estradiol levels, reduction of hypothalamic KISS1 and GnRH expression, and a decrease in serum FSH levels were found in C1QL1-deficient mice. In C1QL1-deficient ovaries, many primordial follicles were recruited and developed into medium follicles but underwent atresia at the large follicle stages, which resulted in depletion of follicle reserve. Depletion of C1QL1 alleviated the inhibitory effect of C1QL1 on granulosa cell apoptosis and the stimulatory effect of C1QL1 on granulosa cell autophagy, which resulted in accumulation in the preantral and early antral follicles and an increase in the atretic follicles. The abnormal profile of endocrine hormones accelerated the intraovarian effect of C1QL1 deficiency and further led to depletion of ovarian reserve. Altogether, this study revealed the expression patterns and the mechanism of action of C1QL1 during folliculogenesis and demonstrated that deficiency of C1QL1 caused ovarian follicular depletion.